High-conductivity graphene copper wire and preparation method thereof

By preparing graphene-copper intermediate alloy and smelting in high-temperature copper liquid, combined with casting, hot extrusion and vacuum annealing treatment, the problem of uneven dispersion of graphene in metal materials is solved, and the excellence of high-conductivity copper wire is achieved Performance and low cost preparation.

CN119216402APending Publication Date: 2024-12-31JIANGSU LANQIER NEW MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411349180.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, when graphene is introduced into metal materials, the agglomeration of powders cannot be achieved uniform dispersion, which is costly to prepare, and the traditional chemical vapor deposition method is complex and expensive.

Method used

By preparing graphene-copper intermediate alloy and adding it to high-temperature copper liquid and re-smelting, combining casting, hot extrusion, drawing processing and secondary vacuum annealing heat treatment, uniform dispersion and stable structure of graphene are achieved.

Benefits of technology

The excellent mechanical properties and electrical conductivity of high-conductivity copper wire are achieved, which simplifies the preparation process, reduces costs, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of copper wire preparation, in particular to a high-conductivity graphene copper wire and a preparation method thereof. A preparation method of a high-conductivity graphene copper wire comprises the steps that graphene-copper intermediate alloy is prepared and added into high-temperature copper liquid to be smelted again, and then through casting, hot extrusion, drawing machining and secondary vacuum annealing heat treatment, uniform dispersion of graphene, a more stable structure and finer grains are achieved. The high-conductivity copper wire prepared by the method shows excellent mechanical property and conductivity. In addition, the preparation method is simple, the preparation time is shortened, the production efficiency is high, and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of copper wire preparation, and in particular to a high-conductivity graphene copper wire and a preparation method thereof. Background Art

[0002] Graphene is a two-dimensional carbon material with a π-bond structure similar to carbon nanotubes and a zero-bandgap metal-like property, and a high charge carrier mobility. Copper and graphene have complementary electrical properties. The charge carrier mobility of graphene is four orders of magnitude higher than that of copper, but the charge carrier density is lower, while the charge carrier density of copper is fourteen orders of magnitude higher than that of graphene. Therefore, under the synergistic effect, the composite interface of the two components will have extremely high conductivity. Studies have shown that when graphene contacts a metal surface such as copper, it still maintains its zero-bandgap characteristics, while inducing Fermi energy transfer, causing an electron doping effect, increasing the free electron concentration in graphene, and obtaining a higher conductivity. Graphene has the strongest electrical and thermal conductivity, and its resistivity is lower than that of copper or silver. Introducing graphene into metal materials can further improve the electrical conductivity and mechanical properties of the material. Realizing the excellent performance of graphene in composite materials through new preparation technologies is one of the current research hotspots.

[0003] At present, graphene powder is generally introduced into metal materials through a mixing method, but due to the agglomeration of powder, it is impossible to obtain uniform dispersion. The preparation of graphene film adopts the chemical vapor deposition method. The carbon atoms generated by the cracking of methane gaseous carbon source at high temperature are adsorbed on the surface of the metal substrate, and then nucleate and grow into "graphene islands", and a continuous graphene film is obtained through the two-dimensional growth and merging of "graphene islands". This method generally requires a high vacuum system, complex atmosphere control and a rapid temperature rise and fall heat treatment system, and the preparation cost is relatively high. Summary of the invention

[0004] The purpose of this application is to provide a high-conductivity graphene copper wire and a preparation method thereof in view of the shortcomings of the current technology. This application prepares a graphene-copper intermediate alloy, adds it to a high-temperature copper liquid for re-smelting, and then achieves uniform dispersion of graphene, a more stable structure, and more refined grains through casting, hot extrusion, drawing, and secondary vacuum annealing heat treatment. The prepared high-conductivity copper wire exhibits excellent mechanical properties and conductive properties. In addition, the preparation method of this application is simple, shortens the preparation time, has high production efficiency, and low cost.

[0005] In a first aspect, the present application provides a method for preparing a high conductivity graphene copper wire, using the following technical solution: A method for preparing a high-conductivity graphene copper wire comprises the following steps: S1. In an argon atmosphere, placing an oxygen-free copper block in a vacuum induction furnace for high-temperature smelting to obtain high-temperature copper liquid; S2, adding the graphene-copper master alloy into the high-temperature copper liquid and smelting again to obtain a graphene-copper melt; S3, pouring the graphene-copper melt into a mold for casting to obtain a copper billet; S4, continuously hot extruding the copper billet at a temperature of 600-650° C. and a pressure of 60-65 MPa to produce a copper wire with a diameter of 20 mm; S5. Drawing a copper wire with a diameter of 20 mm. During the drawing process, when the diameter of the copper wire is drawn to 4 mm-5 mm, a first vacuum annealing heat treatment is performed; when the diameter of the copper wire is drawn to 1 mm, a second vacuum annealing heat treatment is performed, and finally a high-conductivity graphene copper wire is obtained.

[0006] By adopting the above technical scheme, in an argon atmosphere, the oxygen-free copper block is placed in a vacuum induction furnace for high-temperature smelting to obtain a high-temperature copper liquid. The purpose of this step is to melt the oxygen-free copper block into a high-temperature copper liquid to prepare for the subsequent addition and smelting of the graphene-copper master alloy. The graphene-copper master alloy is added to the high-temperature copper liquid and smelted again to obtain a graphene-copper melt. The purpose of this step is to fully mix the graphene-copper master alloy with the high-temperature copper liquid so that the graphene is evenly dispersed in the copper melt, thereby improving the conductive properties and mechanical properties of the high-conductivity copper wire finally obtained. The graphene-copper melt is poured into a mold for casting to obtain a copper billet. The purpose of this step is to solidify the graphene-copper melt into a solid copper billet to prepare for subsequent continuous hot extrusion processing. The copper billet is continuously hot extruded to make a copper wire with a diameter of 20 mm. The purpose of this step is to form a copper wire with a diameter of 20 mm from the copper billet through continuous hot extrusion processing, while refining the grains and improving the mechanical properties and conductive properties of the material. A copper wire with a diameter of 20 mm is drawn and subjected to two vacuum annealing heat treatments to finally obtain a high-conductivity graphene copper wire. The purpose of this step is to further refine the grains through drawing and vacuum annealing heat treatment, and to improve the electrical conductivity and mechanical properties of the copper wire. In summary, the preparation method of the high-conductivity graphene copper wire of the present application achieves uniform dispersion of graphene, a more stable structure, and more refined grains through the steps of preparing graphene-copper intermediate alloy, high-temperature smelting, casting, continuous hot extrusion, drawing and vacuum annealing heat treatment, and the prepared high-conductivity copper wire exhibits excellent mechanical properties and electrical conductivity. In addition, the preparation method of the present application is simple, shortens the preparation time, has high production efficiency and low cost.

[0007] Preferably, in step S1, the mass content of copper in the oxygen-free copper block is not less than 99.99%; the temperature of the high-temperature smelting is 1200° C.-1230° C., and the holding time is 5-6 hours.

[0008] Preferably, the graphene-copper master alloy comprises the following raw materials, measured by mass: 10 parts of graphene oxide, 800 parts of ethanol, 15.4 parts of ethanol copper, 43.6 parts of pure copper powder, 2 parts of hydroxyphenylethanolamine and 130 parts of tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 7.5.

[0009] Preferably, the method for preparing the graphene-copper master alloy comprises the following steps: S41, mixing graphene oxide, hydroxyphenylethanolamine and ethanol according to parts by mass to prepare a graphene oxide dispersion; S42, respectively adding ethanol copper, pure copper powder and tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 7.5 to the graphene oxide dispersion according to their weight fractions, stirring evenly, heating to 53° C. to react for 5-8 hours, concentrating to dryness, and collecting the solid phase; S43, calcining the solid phase at 1200-1230° C. for 3 hours in a reducing atmosphere, and cooling to room temperature to obtain a graphene-copper intermediate alloy.

[0010] By adopting the above technical scheme, in the preparation process of graphene-copper master alloy, the surface of graphene oxide is rich in oxygen-containing functional groups, and hydroxyphenylethanolamine is used to nitrogen-modify graphene oxide, and the nitrogen-containing groups and oxygen-containing functional groups are used to fully disperse the copper element and pure copper powder to obtain a master alloy with smaller particle size and more uniform distribution; thereby further improving the dispersion of the above components in the high-conductivity copper wire finally obtained, achieving uniform dispersion of graphene, more stable structure, and more refined grains, and the prepared high-conductivity copper wire presents excellent mechanical properties and electrical conductivity. The effects and synergistic effects of graphene-copper master alloy are as follows: Improve electrical conductivity: Graphene has excellent electrical conductivity, and adding it to copper wire can significantly improve the electrical conductivity of copper wire. At the same time, the uniform dispersion of graphene makes the internal electron transmission of copper wire smoother, further improving the electrical conductivity. Enhance mechanical properties: Graphene has high strength and hardness, and adding it to copper wire can improve the tensile strength and compressive strength of copper wire, thereby improving the service life of copper wire. Grain refinement: The presence of graphene can promote the grain refinement inside the copper wire, making the microstructure of the copper wire more compact, thereby improving the mechanical properties and electrical conductivity of the copper wire. Reduce costs: By preparing the method of graphene-copper intermediate alloy, the preparation of high-performance copper wire can be achieved at a lower cost. Compared with the traditional method of preparing high-conductivity copper wire, the method of the present application has higher production efficiency and lower cost. In summary, the graphene-copper intermediate alloy in the present application plays a key role in the preparation process of high-conductivity graphene copper wire, achieving uniform dispersion of graphene, more stable structure, and more refined grains, so that the prepared high-conductivity copper wire exhibits excellent mechanical properties and electrical conductivity.

[0011] Preferably, the reducing gas consists of argon and hydrogen, the volume percentage of argon in the reducing gas is 80-85%, and the remainder is hydrogen; the flow rate of the reducing gas is 3.5 L / min.

[0012] Preferably, the graphene oxide has a sheet diameter of 0.5 μm-5 μm and a thickness of 0.8 nm-1.2 nm, and the pure copper powder has a purity of 99.99% and a particle size of 3-5 microns.

[0013] By adopting the above technical scheme, graphene oxide is a two-dimensional nanomaterial with rich oxygen-containing functional groups, and its sheet diameter is 0.5μm-5μm and its thickness is 0.8nm-1.2nm. In the process of preparing graphene-copper master alloy, the oxygen-containing functional groups on the surface of graphene oxide can react with hydroxyphenylethanolamine to achieve nitrogen modification of graphene oxide. At the same time, the oxygen-containing functional groups can also be fully dispersed with copper elements and pure copper powder to form a master alloy with smaller particle size and more uniform distribution. This not only improves the quality of the graphene-copper master alloy, but also facilitates the uniform dispersion of graphene in the high conductivity copper wire finally obtained and the formation of a stable structure. Pure copper powder is another main raw material with a purity of 99.99% and a particle size of 3-5 microns. In the preparation process, pure copper powder and graphene oxide participate in the reaction together to form a graphene-copper master alloy. Since pure copper powder has a higher purity and a smaller particle size, the prepared master alloy has better electrical conductivity and mechanical properties. In addition, pure copper powder can fully disperse with the oxygen-containing functional groups on the surface of graphene oxide, further promoting the uniform dispersion of graphene in high-conductivity copper wires and the formation of a stable structure.

[0014] Preferably, in step S2, the process parameters of the re-smelting are: temperature of 1220-1240°C; stirring time of 130-150 seconds, and holding time of 5-6 minutes.

[0015] Preferably, in step S2, the mass ratio of the graphene-copper master alloy to the high-temperature copper liquid is 1:100.

[0016] By adopting the above technical scheme, firstly, the addition of graphene-copper master alloy can improve the conductivity of copper wire. Graphene is a material with excellent conductivity. Adding it to copper wire can improve the conductivity of copper wire. At the same time, graphene also has good mechanical properties, which can improve the strength and toughness of copper wire. Secondly, the addition of graphene-copper master alloy can improve the processing performance of copper wire, making it easier to process. In addition, graphene can also reduce the wear of copper wire during processing and extend its service life. Finally, the addition of graphene-copper master alloy can improve the stability of copper wire. The presence of graphene can prevent oxidation of copper wire and improve its corrosion resistance. At the same time, graphene can also improve the thermal stability of copper wire, so that it can still maintain good conductivity in high temperature environment. Therefore, the mass fraction ratio of graphene-copper master alloy and high-temperature copper liquid is 1:100, which can not only ensure the uniform dispersion of graphene, but also achieve a more stable structure and more refined grains, thereby preparing a high-conductivity copper wire with excellent mechanical properties and conductivity.

[0017] Preferably, in step S5, the temperature of the first vacuum annealing heat treatment is 600°C-650°C, the time is 4h-5h, and the vacuum degree is 1kPa; the temperature of the second vacuum annealing heat treatment is 400°C-450°C, the time is 2h-3h, and the vacuum degree is 1kPa.

[0018] By adopting the above technical scheme, the first vacuum annealing heat treatment: the first vacuum annealing heat treatment is carried out when the diameter of the copper wire is drawn to 4mm-5mm. The main purpose is to eliminate the stress and lattice distortion generated during the drawing process, so that the internal structure of the copper wire is more stable. At the same time, annealing treatment at high temperature can promote the interface bonding between graphene and the copper matrix and improve the overall performance of the composite material. In addition, appropriate annealing temperature and time can also refine the grains of the copper wire, thereby improving its mechanical properties and electrical conductivity. The second vacuum annealing heat treatment: the second vacuum annealing heat treatment is carried out when the diameter of the copper wire is drawn to 1mm. At this time, the copper wire is close to the final size. Annealing heat treatment again can further eliminate residual stress, optimize the grain structure, and improve the mechanical properties and electrical conductivity of the copper wire. Compared with the first annealing heat treatment, the second annealing heat treatment has a lower temperature and a shorter time, which can avoid excessive interface reaction between graphene and the copper matrix caused by excessive temperature, thereby maintaining the excellent performance of the composite material. In summary, the synergistic effect of the two vacuum annealing heat treatments is mainly reflected in the following aspects: by gradually reducing the annealing temperature and time, the internal structure of the copper wire is gradually optimized, so that its mechanical properties and electrical conductivity are significantly improved. While maintaining a good interface between graphene and the copper matrix, excessive interface reaction caused by excessive temperature is avoided, thereby maintaining the excellent performance of the composite material. By selecting reasonable annealing process parameters, the preparation time is shortened, the production efficiency is improved, and the cost is reduced.

[0019] In a second aspect, the present application provides a high conductivity graphene copper wire, which adopts the following technical solution: As a general technical concept, the present application also provides a high-conductivity graphene copper wire prepared by the above-mentioned method for preparing a high-conductivity graphene copper wire.

[0020] In summary, the beneficial technical effects of this application are: 1. High conductivity: By adding graphene-copper master alloy, the prepared copper wire has higher conductivity. As a material with excellent conductive properties, the uniform dispersion of graphene in copper wire can significantly improve the conductivity of copper wire.

[0021] 2. Excellent mechanical properties: The addition of graphene can not only improve the conductivity of copper wire, but also enhance its mechanical properties. The high specific strength and high hardness of graphene make the copper wire more stable and less likely to break when subjected to external forces.

[0022] 3. Low cost: The preparation method of the present application is simple and has high production efficiency, and a large amount of high-conductivity copper wire can be produced in a short time, thereby reducing the production cost.

[0023] 4. Stable structure: Through steps such as casting, hot extrusion, drawing and secondary vacuum annealing heat treatment, graphene is evenly dispersed in the copper wire, forming a more stable structure and further improving the performance of the copper wire.

[0024] 5. Grain refinement: The preparation method of the present application can make the grains of the copper wire more refined, thereby improving the mechanical properties and electrical conductivity of the copper wire.

[0025] 6. Environmentally friendly: In the preparation process of the present application, oxygen-free copper blocks and argon atmosphere are used to avoid environmental pollution.

[0026] 7. Wide application: Since the high conductivity copper wire prepared in this application has excellent electrical conductivity and mechanical properties, it can be widely used in the fields of electricity, electronics, communications, etc. DETAILED DESCRIPTION

[0027] The embodiments of the present application will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be considered to limit the scope of the present application. If the specific conditions are not specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially. Graphene oxide was purchased from XF002-2 (sheet diameter: 0.5μm-5μm, thickness: 0.8nm-1.2nm) of Xianfeng Nano.

[0028] In the following examples, preparation examples and comparative preparation examples, 1 part means 100 g.

[0029] Preparation Example 1 Preparation of graphene-copper master alloy A graphene-copper master alloy comprises the following raw materials, by mass: 10 parts of graphene oxide, 800 parts of ethanol, 15.4 parts of ethanol copper, 43.6 parts of pure copper powder, 2 parts of hydroxyphenylethanolamine and 130 parts of tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 7.5, wherein the graphene oxide has a sheet diameter of 0.5 μm-5 μm and a thickness of 0.8 nm-1.2 nm, and the pure copper powder has a purity of 99.99% and a particle size of 3-5 microns; The method for preparing the graphene-copper master alloy comprises the following steps: S41, mixing graphene oxide, hydroxyphenylethanolamine and ethanol according to parts by mass to prepare a graphene oxide dispersion; S42, respectively adding ethanol copper, pure copper powder and tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 7.5 to the graphene oxide dispersion according to their weight fractions, stirring evenly, heating to 53° C. to react for 5-8 hours, concentrating to dryness, and collecting the solid phase; S43. calcining the solid phase at 1220° C. for 3 hours in a reducing atmosphere, and cooling to room temperature to obtain a graphene-copper intermediate alloy, wherein the reducing gas consists of argon and hydrogen, the volume percentage of argon in the reducing gas is 83%, and the remainder is hydrogen; the flow rate of the reducing gas is 3.5 L / min.

[0030] Preparation Comparative Example 1 10 parts of graphene oxide and 50 parts of pure copper powder are stirred and mixed evenly to obtain a mixture of graphene oxide and pure copper powder, wherein the graphene oxide has a sheet diameter of 0.5 μm-5 μm and a thickness of 0.8 nm-1.2 nm, and the pure copper powder has a purity of 99.99% and a particle size of 3-5 microns.

[0031] Example 1 A method for preparing a high-conductivity graphene copper wire comprises the following steps: S1. Under an argon atmosphere, 20 kg of oxygen-free copper block with a purity of 99.99% is placed in a vacuum induction furnace for high-temperature smelting. The high-temperature smelting temperature is 1200° C. and the holding time is 6 hours to obtain high-temperature copper liquid; S2, adding the graphene-copper master alloy to the high-temperature copper liquid and smelting it again, the mass ratio of the graphene-copper master alloy to the high-temperature copper liquid is 1:100, and the process parameters of the re-smelting are: temperature is 1220° C.; stirring time is 150 seconds, and holding time is 6 minutes, to obtain a graphene-copper melt; S3, pouring the graphene-copper melt into a mold for casting to obtain a copper billet; S4, continuously hot extruding the copper billet at a temperature of 600° C. and a pressure of 65 MPa to produce a copper wire with a diameter of 20 mm; S5. Drawing a copper wire with a diameter of 20 mm. During the drawing process, when the diameter of the copper wire is drawn to 4 mm, a first vacuum annealing heat treatment is performed, and the temperature of the first vacuum annealing heat treatment is 600° C., the time is 5 hours, and the vacuum degree is 1 kPa; when the diameter of the copper wire is drawn to 1 mm, a second vacuum annealing heat treatment is performed, and the temperature of the second vacuum annealing heat treatment is 400° C., the time is 3 hours, and the vacuum degree is 1 kPa, and finally a high conductivity graphene copper wire is obtained.

[0032] Example 2 A method for preparing a high-conductivity graphene copper wire comprises the following steps: S1. In an argon atmosphere, 20 kg of oxygen-free copper block with a purity of 99.99% is placed in a vacuum induction furnace for high-temperature smelting. The high-temperature smelting temperature is 1230° C. and the holding time is 5 hours to obtain high-temperature copper liquid; S2, adding the graphene-copper master alloy to the high-temperature copper liquid and smelting it again, the mass ratio of the graphene-copper master alloy to the high-temperature copper liquid is 1:100, and the process parameters of the re-smelting are: temperature is 1240° C.; stirring time is 130 seconds, and holding time is 5 minutes, to obtain a graphene-copper melt; S3, pouring the graphene-copper melt into a mold for casting to obtain a copper billet; S4, continuously hot-extruding the copper billet at a temperature of 650° C. and a pressure of 60 MPa to produce a copper wire with a diameter of 20 mm; S5. Drawing a copper wire with a diameter of 20 mm. During the drawing process, when the diameter of the copper wire is drawn to 5 mm, a first vacuum annealing heat treatment is performed, and the temperature of the first vacuum annealing heat treatment is 650° C., the time is 4 hours, and the vacuum degree is 1 kPa; when the diameter of the copper wire is drawn to 1 mm, a second vacuum annealing heat treatment is performed, and the temperature of the second vacuum annealing heat treatment is 450° C., the time is 2 hours, and the vacuum degree is 1 kPa, and finally a high conductivity graphene copper wire is obtained.

[0033] Example 3 A method for preparing a high-conductivity graphene copper wire comprises the following steps: S1. In an argon atmosphere, 20 kg of oxygen-free copper block with a purity of 99.99% is placed in a vacuum induction furnace for high-temperature smelting. The high-temperature smelting temperature is 1220° C. and the holding time is 5.6 h to obtain high-temperature copper liquid; S2, adding the graphene-copper master alloy to the high-temperature copper liquid and smelting it again, the mass ratio of the graphene-copper master alloy to the high-temperature copper liquid is 1:100, and the process parameters of the re-smelting are: temperature is 1230° C.; stirring time is 140 seconds, and holding time is 5.5 minutes, to obtain a graphene-copper melt; S3, pouring the graphene-copper melt into a mold for casting to obtain a copper billet; S4, continuously hot-extruding the copper billet at a temperature of 630° C. and a pressure of 63 MPa to produce a copper wire having a diameter of 20 mm; S5. Drawing a copper wire with a diameter of 20 mm. During the drawing process, when the diameter of the copper wire is drawn to 5 mm, a first vacuum annealing heat treatment is performed, and the temperature of the first vacuum annealing heat treatment is 630° C., the time is 4.5 h, and the vacuum degree is 1 kPa; when the diameter of the copper wire is drawn to 1 mm, a second vacuum annealing heat treatment is performed, and the temperature of the second vacuum annealing heat treatment is 430° C., the time is 2.5 h, and the vacuum degree is 1 kPa, and finally a high conductivity graphene copper wire is obtained.

[0034] Comparative Example 1 The same as Example 3, except that, in step S2, the mass ratio of the graphene-copper master alloy to the high-temperature copper liquid is 1:80.

[0035] Comparative Example 2 The same as Example 3, except that, in step S2, the mass ratio of the graphene-copper master alloy to the high-temperature copper liquid is 1:120.

[0036] Comparative Example 3 The same as Example 3, except that an equal amount of the mixture prepared in Preparation Comparative Example 1 is used to replace the graphene-copper master alloy.

[0037] Comparative Example 4 The same as Example 3, except that in step S5, a copper wire with a diameter of 20 mm is drawn. During the drawing process, when the diameter of the copper wire is drawn to 1 mm, a vacuum annealing heat treatment is performed. The temperature of the vacuum annealing heat treatment is 430°C, the time is 7 hours, and the vacuum degree is 1 kPa, and finally a high conductivity graphene copper wire is obtained.

[0038] Performance Testing The high conductivity graphene copper wires prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were sampled and subjected to the following performance tests; Test of tensile strength and yield strength: Test according to GB / T2281-2010; The conductivity test is carried out in accordance with GB / T30482-2007.

[0039] Table 1 Performance test project Tensile strength / MPa Yield strength / MPa Conductivity / %IACS Example 1 547 523 129 Example 2 562 531 136 Example 3 555 527 132 Comparative Example 1 473 453 113 Comparative Example 2 480 441 114 Comparative Example 3 453 417 105 Comparative Example 4 492 456 120 Analyzing the data in Table 1, we can see that: 1) The high-conductivity graphene copper wires obtained in Examples 1 to 3 are prepared by preparing a graphene-copper intermediate alloy, which is then added to a high-temperature copper liquid for re-smelting, and then subjected to casting, hot extrusion, drawing processing and secondary vacuum annealing heat treatment to achieve uniform dispersion of graphene, a more stable structure, and more refined grains. The prepared high-conductivity copper wires exhibit excellent mechanical properties and conductive properties.

[0040] 2) The performance comparison analysis of the high conductivity graphene copper wire prepared in combination with Example 3 and Comparative Examples 1-2 shows that the mass ratio of the graphene-copper master alloy to the high-temperature copper liquid is 1:100, which can not only ensure the uniform dispersion of graphene, but also achieve a more stable structure and more refined grains, thereby preparing a high conductivity copper wire with excellent mechanical properties and conductive properties.

[0041] 3) The performance comparison analysis of the high conductivity graphene copper wire prepared in Example 3 and Comparative Example 3 shows that in the preparation process of the graphene-copper master alloy, the graphene oxide surface has abundant oxygen-containing functional groups, and the graphene oxide is nitrogen-modified by hydroxyphenylethanolamine, and the copper element and pure copper powder are fully dispersed by nitrogen-containing groups and oxygen-containing functional groups to obtain a master alloy with smaller particle size and more uniform distribution; thereby further improving the dispersibility of the above components in the high conductivity copper wire finally obtained, achieving uniform dispersion of graphene, a more stable structure, and more refined grains, and the prepared high conductivity copper wire exhibits excellent mechanical properties and conductive properties.

[0042] 4) The performance comparison analysis of the high conductivity graphene copper wire obtained in combination with Example 3 and Comparative Example 4 shows that the use of secondary vacuum annealing heat treatment and the synergistic effect between the two vacuum annealing heat treatments: by gradually reducing the annealing temperature and time, the internal structure of the copper wire is gradually optimized, so that its mechanical properties and conductivity are significantly improved. While maintaining a good interface bonding between graphene and the copper matrix, excessive interface reaction caused by excessively high temperatures is avoided, thereby maintaining the excellent performance of the composite material. By selecting reasonable annealing process parameters, the preparation time is shortened, the production efficiency is improved, and the cost is reduced.

[0043] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.

Claims

1. A method for preparing high conductivity graphene copper wire, characterized in that: The following steps are involved: S1. In an argon atmosphere, placing an oxygen-free copper block in a vacuum induction furnace for high-temperature smelting to obtain high-temperature copper liquid; S2, adding the graphene-copper master alloy into the high-temperature copper liquid and smelting again to obtain a graphene-copper melt; S3, pouring the graphene-copper melt into a mold for casting to obtain a copper billet; S4, continuously hot extruding the copper billet at a temperature of 600-650° C. and a pressure of 60-65 MPa to produce a copper wire with a diameter of 20 mm; S5. Drawing a copper wire with a diameter of 20 mm. During the drawing process, when the diameter of the copper wire is drawn to 4 mm-5 mm, a first vacuum annealing heat treatment is performed; when the diameter of the copper wire is drawn to 1 mm, a second vacuum annealing heat treatment is performed, and finally a high-conductivity graphene copper wire is obtained.

2. The method for preparing a high conductivity graphene copper wire according to claim 1, characterized in that: In step S1, the mass content of copper in the oxygen-free copper block is not less than 99.99%; the temperature of the high-temperature smelting is 1200° C.-1230° C., and the insulation time is 5-6 hours.

3. The method for preparing a high conductivity graphene copper wire according to claim 1, characterized in that: The graphene-copper master alloy comprises the following raw materials by weight: 10 parts of graphene oxide, 800 parts of ethanol, 15.4 parts of ethanol copper, 43.6 parts of pure copper powder, 2 parts of hydroxyphenylethanolamine and 130 parts of tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 7.

5.

4. The method for preparing a high conductivity graphene copper wire according to claim 3, characterized in that: The method for preparing the graphene-copper master alloy comprises the following steps: S41, mixing graphene oxide, hydroxyphenylethanolamine and ethanol according to parts by mass to prepare a graphene oxide dispersion; S42, respectively adding ethanol copper, pure copper powder and tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 7.5 to the graphene oxide dispersion according to their weight fractions, stirring evenly, heating to 53° C. to react for 5-8 hours, concentrating to dryness, and collecting the solid phase; S43, calcining the solid phase at 1200-1230° C. for 3 hours in a reducing atmosphere, and cooling to room temperature to obtain a graphene-copper intermediate alloy.

5. The method for preparing a high conductivity graphene copper wire according to claim 4, characterized in that: The reducing gas is composed of argon and hydrogen, the volume percentage of argon in the reducing gas is 80-85%, and the remainder is hydrogen; the flow rate of the reducing gas is 3.5L / min.

6. The method for preparing a high conductivity graphene copper wire according to claim 3, characterized in that: The sheet diameter of the graphene oxide is 0.5 μm-5 μm and the thickness is 0.8 nm-1.2 nm. The purity of the pure copper powder is 99.99% and the particle size is 3-5 microns.

7. The method for preparing a high conductivity graphene copper wire according to claim 1, characterized in that: In step S2, the process parameters of the re-smelting are: temperature of 1220-1240°C; stirring time of 130-150 seconds, and holding time of 5-6 minutes.

8. The method for preparing a high conductivity graphene copper wire according to claim 1, characterized in that: In step S2, the mass ratio of the graphene-copper master alloy to the high-temperature copper liquid is 1:

100.

9. The method for preparing a high conductivity graphene copper wire according to claim 1, characterized in that: In step S5, the first vacuum annealing heat treatment is performed at a temperature of 600°C-650°C, for 4h-5h, and at a vacuum degree of 1kPa; the second vacuum annealing heat treatment is performed at a temperature of 400°C-450°C, for 2h-3h, and at a vacuum degree of 1kPa.

10. A high conductivity graphene copper wire, characterized in that: The high-conductivity graphene copper wire is prepared by the preparation method of a high-conductivity graphene copper wire according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing graphene / aluminum alloy composite material

    CN105112702A

  • Preparation method for graphene reinforced copper-matrix electrical contact material

    CN105695776A

  • Preparation method of Cu / C composite wire rod

    CN108320834A

  • Graphene compound for lubricating oil additive, preparation method and application thereof

    CN112625776A

  • High-strength aluminum alloy and preparation method and application thereof

    CN116855798A